Quantifying the Contribution of Organisms to the Provision of Ecosystem Services - Luck, Gary (2009)
Research on ecosystem services has grown rapidly over the last decade. Two conceptual frameworks have been published to guide ecological assessments of organisms that deliver services?the concepts of service-providing units (SPUs) and ecosystem service providers (ESPs). Here, we unite these frameworks and present an SPU-ESP continuum that offers a coherent conceptual approach for synthesizing the latest developments in ecosystem service research, and can direct future studies at all levels of organization. In particular, we show how the service-provider concept can be applied at the population, functional group, and community levels. We strongly emphasize the need to identify and quantify the organisms and their characteristics (e.g., functional traits) that provide services, and to assess service provision relative to the demands of human beneficiaries. We use key examples from the literature to illustrate the new approach and to highlight gaps in knowledge, particularly in relation to the impact of species interactions and ecosystem dynamics on service provision.